2015
DOI: 10.2147/copd.s78952
|View full text |Cite
|
Sign up to set email alerts
|

Do females behave differently in COPD exacerbation?

Abstract: IntroductionLittle is known about whether there is any sex effect on chronic obstructive lung disease (COPD) exacerbations. This study is intended to describe the possible sex-associated differences in exacerbation profile in COPD patients.MethodsA total of 384 COPD patients who were hospitalized due to exacerbation were evaluated retrospectively for their demographics and previous and current exacerbation characteristics.ResultsThe study was conducted on 109 (28%) female patients and 275 (72%) male patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
6
22
3
1
Order By: Relevance
“…This finding concurred with previous results, showing females had lower 30-day all-cause readmissions 43 and fewer ICU admissions due to COPD exacerbation in the previous year. 21 Males, based on review and retrospective study, in accordance with our estimates, had a higher frequency of readmission. 44,45 Because females were less likely to self-report COPD and have COPD as a primary diagnosis, when women were readmitted within 30 days their reasons for readmission may not have been caused by COPD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding concurred with previous results, showing females had lower 30-day all-cause readmissions 43 and fewer ICU admissions due to COPD exacerbation in the previous year. 21 Males, based on review and retrospective study, in accordance with our estimates, had a higher frequency of readmission. 44,45 Because females were less likely to self-report COPD and have COPD as a primary diagnosis, when women were readmitted within 30 days their reasons for readmission may not have been caused by COPD.…”
Section: Discussionsupporting
confidence: 90%
“…7,11,19 Males were more likely to be readmitted, 19,20 whereas females had fewer comorbidities and might be undertreated for COPD, itself. 21 Although gender plays an important role in COPD readmission, few studies have navigated how gender might affect the COPD-related 30-day readmission rate among patients with and without additional comorbidities. We hypothesized that both male and female COPD patients with comorbidities were more likely to be readmitted, compared to male patients without comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…The present study, as in the study by Kilic et al,20 showed that women experienced significantly more exacerbations. However, the increase of exacerbations in relation to higher age, found in other studies,7,9 was not found in this sample.…”
Section: Discussionsupporting
confidence: 87%
“…With regard to disease characteristics, more men than women were diagnosed with comorbidities, except for osteoporosis and depression/anxiety, which occurred more frequently in women, which was also reported by Aryal et al4 Differences in comorbidity profile were also found by Kilic et al,20 who reported that women, to a larger extent, had sleep disorder, chronic kidney disease, anemia, and gastroesophageal reflux disease 20. The present study, as in the study by Kilic et al,20 showed that women experienced significantly more exacerbations.…”
Section: Discussionsupporting
confidence: 63%
“…As in other studies, the male sex was a risk factor of exacerbation due to the smoking habits. However, other studies have reported a higher risk of exacerbation in females [ 30 ].…”
Section: Discussionmentioning
confidence: 97%